DETERMINASI FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN APLIKASI OJEK ONLINE - Muhamad Sidik; Solechan, Achmad (Jurnal Ekonomi Bisnis dan Akuntansi, 2021)
This study aims to analyze the factors that influence the decision to use the online motorcycle taxi application, which in this study takes a case study on the Grab application in the city of Semarang. The technique for determining data collection in this research is using a questionnaire that is distributed to 100 people (users) or users of the Grab online motorcycle taxi application with objects in the city of Semarang. The method of collecting respondents was using the accidental sampling method, namely collecting data from consumers who happened to use Grab's services in Semarang. This research uses quantitative data analysis techniques using multiple linear regression. Based on the study and processing of statistical data, it was found that the price had a positive effect on the decisions of online motorcycle taxi users. Promotion also has a positive and significant effect on the decisions of online motorcycle taxi application users. And other findings obtained that the quality of service has a positive and significant effect on the decisions of online motorcycle taxi application users. The suggestion from this research is that the Grab tariff needs to be considered so that the tariff is cheap, in accordance with the benefits and adjusted to the tariff for other online motorcycle taxi services. Promotional indicators that need to be considered are the reach of information and promotions that need to be expanded, attractive advertising stars, online motorcycle taxi services are easy to remember and the quality of the messages conveyed and advertising messages are easy to understand. Service quality indicators that need to be considered include: the appearance of Gojek partners is neat, Gojek partners work according to work schedules, responsive in hearing consumer complaints, able to serve consumers well and pay attention and communicate in a friendly manner. Keywords: price, promotion, service quality, and decision to use online motorcycle taxi applications